1995
DOI: 10.1007/bf00037027
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of the SLG gene is not correlated with the self-incompatibility phenotype in the class II S haplotypes of Brassica oleracea

Abstract: In Brassica, the S-locus glycoprotein (SLG) gene has been strongly implicated in the self-incompatibility reaction. Several alleles of this locus have been sequenced, and accordingly grouped as class I (corresponding to dominant S-alleles) and class II (recessive). We recently showed that a self-compatible (Sc) line of Brassica oleracea expressed a class II-like SLG (SLG-Sc) gene. Here, we report that the SLG-Sc glycoprotein is electrophoretically and immunochemically very similar to the recessive SLG-S15 glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…present but significantly rearranged in) the S 2 haplotype. Gaude et al (1995) have shown that the S 2 homozygous line expresses a very low level of SLG, whereas SLG levels are significantly higher and comparable with those of S 15 in the S 5 homozygous line. Figure 4 shows that in the S 15 haplotype, SLGA is strongly expressed and accounts for 79.5% of stigma SLG, whereas SLGB only encodes 20.5%.…”
Section: Do Other S Haplotypes Contain Three S Gene Family Members?mentioning
confidence: 82%
“…present but significantly rearranged in) the S 2 haplotype. Gaude et al (1995) have shown that the S 2 homozygous line expresses a very low level of SLG, whereas SLG levels are significantly higher and comparable with those of S 15 in the S 5 homozygous line. Figure 4 shows that in the S 15 haplotype, SLGA is strongly expressed and accounts for 79.5% of stigma SLG, whereas SLGB only encodes 20.5%.…”
Section: Do Other S Haplotypes Contain Three S Gene Family Members?mentioning
confidence: 82%
“…SLG, which apparently was formed by a duplication of the SRK gene (Tantikanjana et al, 1993), is found in Brassica and Raphanus spp (Sakamoto et al, 1998). It occurs in tight genetic and physical linkage to the SRK and SCR genes and is expressed at high levels in plants homozygous for most Brassica S haplotypes, but it is absent (Okazaki et al, 1999) or expressed at low levels (Tantikanjana et al, 1993(Tantikanjana et al, , 1996Gaude et al, 1995;Cabrillac et al, 1999) in plants homozygous for a few S haplotypes. An SRKb-related sequence that may be genetically linked to the S locus was detected on DNA gel blots of A. lyrata Sa and Sb homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…The pollen-pistil recognition takes place by the interaction between membrane-spanning Ser-Thr protein kinase in the stigma, i.e., S-locus receptor kinase (Stein et al, 1991;Takasaki et al, 2000), and low-molecular weight Cys-rich protein in pollen, i.e., S-locus protein 11(SP11)/S-locus Cys-rich protein (SCR) (Schopfer et al, 1999;Suzuki et al, 1999). The genes encoding these molecules, i.e., SRK and SP11/SCR (referred to as SP11 hereafter), are located in the S locus, and another molecule encoded in the S locus is S-locus glycoprotein (SLG), the function of which in self-incompatibility is still controversial (Gaude et al, 1995;Okazaki et al, 1999;Dixit et al, 2000;Suzuki et al, 2000;Takasaki et al, 2000;Silva et al, 2001). The alleles of SRK, SP11, and SLG are transmitted to the progeny as one set named S haplotype.…”
Section: Introductionmentioning
confidence: 99%